Stationary and mobile particulate matter concentration measurement in Miskolc - Báthory, Csongor; Pecsmány, Péter; Szalontai , Lajos; Palotás, Árpád Bence (International Journal of Engineering and Management Sciences, 2019)
A stationary and mobile device based on a low-cost dust sensor (Plantower PMS7003) was used to study particulate matter (PM) concentration in Miskolc. The stationary device was placed at the automatic monitoring station of the National Air Quality Measurement Network (OLM) in Martintelep, Miskolc. The mobile device was used to walk 4 streets along a square route with a total length of 800 m. Measurements were made on two days (September 9 and 11) between 7am and 9am, which according to preliminary experience coincided with the morning rush hour. The access route includes the OLM monitoring station, a busy road, two bypasses, a parking lot, and a smaller roadway blocked by traffic. The measured PM1, PM2.5, PM10 concentrations of the mobile device were interpolated on a circuit-by-circuit basis in ArcGIS, and conclusions were drawn for the area. The concentration of stationary and mobile devices was compared.